Avaliação neuropsicológica de crianças com epilepsia pregressa - Lourenceti, Maria Dalva (2010)
This study aimed to investigate neuropsychologic functions of epileptic children in remission. 28 children participated, of both gender, with the ages between 7 to 12 years old, from first to sixty grade of elementar school, with good school performance, divided into two groups: GI, 14 children that received epileptic treatment at least for two years in the past, in the remission period, nowadays without medication, and GII: control group, with 14 nonepileptic children, without neurological problems, matched in according to gender, age and academic level with GI. The instruments used were the Weschsler Intelligent Scale for children (WECHSLER, 2000), Raven Test Progressive Colored Matrices (RAVEN, 1974), Neuropsychological Exam (TABAQUIM, 2006) e Wisconsin (HEATON et al, 2005), and Single Photon Emission Computer Tomography (SPECT). The results were registered and statistically analyzed in order to compare each group performance in tests that measure neuropsychological functions. The results showed medium and above GI s mental level, characterizing significant logic-space-time resources. Inferior percentage in the executive dominium was identified about persevering, categorical and conceptual mistakes. Tasks that demanded verbal comprehension, perceptual organization, distraction resistance and process velocity were more difficult to the experimental group. Considering the scores variability, there was statistically significant difference of the attention and verbal comprehension when the groups were compared. In the analysis of categorical variables, the study attested the sensorial-perceptual-motors organization proofs were significant when the groups were compared. The study concluded that tasks that required superior cortical functions from parietal-temporal-occipital associative areas, necessary for school learning, were demonstrated prejudiced, suggesting impairment from the epilepsy. Thus, the condition of the children with previous epilepsy history have risks of neuropsychological alterations that are sensible to the academic learning.